2011
DOI: 10.1016/j.ajpath.2010.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acids Induce Inflammatory Genes in Hepatocytes

Abstract: Inflammation contributes to liver injury during cholestasis. The mechanism by which cholestasis initiates an inflammatory response in the liver, however, is not known. Two hypotheses were investigated in the present studies. First, activation of Toll-like receptor 4 (TLR4), either by bacterial lipopolysaccharide or by damage-associated molecular pattern molecules released from dead hepatocytes, triggers an inflammatory response. Second, bile acids act as inflammagens, and directly activate signaling pathways i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
217
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 418 publications
(243 citation statements)
references
References 67 publications
8
217
0
1
Order By: Relevance
“…This massive accumulation of bile acids in hepatocytes might initiate a negative-feedback mechanism that results in the observed gene expression reduction. Simultaneously, accumulation of toxic intracellular bile acid levels resulted in cell death, necrosis, and induction of inflammatory mediators (46,47). We supposed that necrosis and leakage of hepatocellular contents explained the increased serum TBA levels despite the CYP7A1 and CYP8B1 gene repression in INH-LPS-cotreated animals.…”
Section: Discussionmentioning
confidence: 98%
“…This massive accumulation of bile acids in hepatocytes might initiate a negative-feedback mechanism that results in the observed gene expression reduction. Simultaneously, accumulation of toxic intracellular bile acid levels resulted in cell death, necrosis, and induction of inflammatory mediators (46,47). We supposed that necrosis and leakage of hepatocellular contents explained the increased serum TBA levels despite the CYP7A1 and CYP8B1 gene repression in INH-LPS-cotreated animals.…”
Section: Discussionmentioning
confidence: 98%
“…In the last decade, a number of studies have suggested that bile acids may injure liver cells in cholestatic liver disease, not by a direct toxic effects as a detergent, but by initiating a cytokine-mediated inflammatory response [1,2]. While there is little doubt that bile acids can injure mitochondria, produce oxidative stress and initiate Fas-dependent apoptosis, these observations have been derived primarily from in-vitro studies in isolated cell systems where the concentrations have exceeded those normally found in the serum or liver of cholestatic animal models or patients with cholestatic liver diseases [3,4,5].…”
mentioning
confidence: 99%
“…Allen et al [1] have shown that the exposure of hepatocytes in culture to levels of bile acids (both toxic and non-toxic) that are seen in-vivo, results in significant increases in mRNA expression of pro-inflammatory cytokines, particularly CXCL2 (MIP-2) and CXCL1 (KC). Importantly, toll-like receptor 4 was not involved in the initiation of this acute inflammatory response [1]. …”
mentioning
confidence: 99%
“…Besides their established role in metabolism, they also act as signaling molecules with systemic endocrine functions [2]. Thus, BAs are involved in cell-signaling receptors such as farnesoid X receptors and G-protein-coupled receptors, making them important for the biotechnological production of new steroid drugs [3].…”
Section: Introductionmentioning
confidence: 99%